PENERAPAN PEMBELAJARAN DARING MELALUI PLATFORM DISCORD CABANG OLAHRAGA ATLETIK LARI 100 METER TERHADAP SISWA SMP NEGERI 2 REJANG LEBONG - Ahsani Taqwim; Widya Handayani; Adi Riyanto; Sarwan Hamid; Muhammad Khoirudin; Rizky Darmawan (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2023)
This class action research (CAR) aims to investigate the effectiveness of implementing online learning through the Discord platform in the 100-meter athletics sport for students of SMP Negeri 2 Rejang Lebong. This research was conducted in two cycles, with each cycle consisting of four stages, namely planning, implementing, observing and reflecting. The research subjects were students of SMP Negeri 2 Rejang Lebong. Data collection methods used are observation and tests. The results of the study show that the application of online learning through the Discord platform in the 100-meter athletics branch can increase students' knowledge in running. There was an increase in knowledge related to running techniques. In addition, the use of the Discord platform also has a positive impact on student motivation and participation in learning. Based on the research results, it can be concluded that the application of online learning through the Discord platform in the 100-meter athletics branch can improve student skills and have a positive impact on student motivation and participation in learning. Therefore, it is recommended that teachers use online platforms such as Discord in teaching in the future